Do local attitudes change with the exposure and the status of the migrants? - Biagi, Bianca; Lambiri , Dionysia; Meleddu, Marta (REGION, 2025)
Attitudes and perceptions regarding refugees and migrants play a vital role in the integration potential of newcomers and reflect policies and policy changes. This paper investigates how the exposure of urban communities to the presence of refugees and migrants in their local neighbourhoods affects their evaluation of the potential for migrant integration in the host country. Furthermore, it investigates the existence of a bias in the awareness of the presence of refugees and whether these evaluations change according to the status of the migrant. Using a unique dataset on the individual perceptions of residents of the Greek capital Athens, the analysis shows a positive effect of perceived presence and contends that perceptions of the size of refugee and migrant populations are more consequential for the formation of attitudes than the actual size. Moreover, residents tend to be more favourably disposed towards those recognised as refugees than they are towards permanent migrants.